Binding interactions of mixed ligand copper(II) amino acid Schiff base complexes with biological targets: Spectroscopic evaluation and molecular docking. (30th January 2017) - Theetharappan, M.; Subha, L.; Balakrishnan, C.; Neelakantan, M.A.
Abstract: Three mixed ligand copper(II) complexes [Cu( o ‐vanillin‐l ‐tryptophan Schiff base)(diimine)] (diimine =2, 2′‐bipyridine (1 ), 1, 10‐phenanthroline (2 ) and 5, 6‐dimethyl‐1, 10‐phenanthroline(3 )) were synthesized and characterized using analytical and spectral methods. The molecular structures of1 –3 were optimized using density functional theory (DFT) at B3LYP/LanL2DZ levels in the gas phase. Spectral and DFT studies suggest a distorted square pyramidal geometry around the copper ion. Binding interactions of1 –3 with calf thymus DNA and bovine serum albumin protein were studied using UV–visible and fluorescence spectroscopies, viscometric titrations and cyclic voltammetry and also using molecular docking analysis. Studies of the binding of the complexes with calf thymus DNA reveal intercalation, which is supported by molecular docking simulation. The DNA cleavage nature of1 –3 with pUC19 DNA shows that the complexes can cleave DNA without any external agents, and the efficiency follows the order1 > 3 > 2 . Synchronous and three‐dimensional fluorescence spectral studies suggest that the secondary structures of the protein are altered by the complexes. Antioxidant studies reveal that the complexes have significant radical scavenging activity against DPPH. In vitro cytotoxic activity of the complexes was evaluated against breast cancer cells (MCF‐7), revealing that complex2 exhibits higher cytotoxicity than the other complexes. Nuclear chromatin condensation and fragmentation were observed with DAPI staining assay. The mitochondrial membrane potential damage was studied by FITC staining assay. Flow cytometric analysis suggests that all the metal complexes induce cell apoptosis. Abstract : Mixed ligand copper(II) complexes containing a Schiff base and diimine co‐ligands were synthesized and characterized. Binding interactions of these complexes with DNA and bovine serum albumin protein were evaluated. DAPI and FITC staining assays were used to study the cytotoxicity.